2015
DOI: 10.1039/c5cy00537j
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of a statin precursor in high space-time yield by a new aldehyde-tolerant aldolase identified from Lactobacillus brevis

Abstract: A novel 2-deoxyribose-5-phosphate aldolase (LbDERA) was identified from Lactobacillus brevis, with high activity, excellent thermostability and high tolerance against aldehyde substrates. The half-lives of LbDERA incubated in 300 mM acetaldehyde and chloroacetaldehyde were 37.3 and 198 min, respectively, which are 2-and 7-fold higher than those of EcDERA from Escherichia coli. The crystal structure of LbDERA determined at 1.95 Å resolution revealed a stable quaternary structure which might account for its exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 30 publications
4
39
0
Order By: Relevance
“…More than 80% of its initial activity was retained after 67 h of incubation at temperatures in the range between 20 and 40 °C, with highest residual activity at 20–25 °C (≈ 87%) (Fig. S4), rendering the DERA Tm more thermostable than the corresponding DERA from Lactobacillus brevis . It was found that the residual enzyme activity was practically constant (>80%) within the pH range from 5.4 to 8.0 and 24 h of incubation, which also is in accordance with previous investigations .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…More than 80% of its initial activity was retained after 67 h of incubation at temperatures in the range between 20 and 40 °C, with highest residual activity at 20–25 °C (≈ 87%) (Fig. S4), rendering the DERA Tm more thermostable than the corresponding DERA from Lactobacillus brevis . It was found that the residual enzyme activity was practically constant (>80%) within the pH range from 5.4 to 8.0 and 24 h of incubation, which also is in accordance with previous investigations .…”
Section: Resultssupporting
confidence: 90%
“…By using achiral substrates, such as chloroacetaldehyde and acetaldehyde, DERA catalyzes a sequential aldol addition that results in an enantiomerically pure lactol, (3 R ,5 R )‐6‐chloro‐2,4,6‐trideoxyhexose . This 2,4,6‐trideoxyhexose is a valuable chiral synthon for HMG‐CoA reductase inhibitors, collectively known as statins, and used for the production of cholesterol‐lowering drugs, such as atorvastatin and rosuvastatin .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EA01524.86509.1137 c Maximal activity at 200 mM(Kim et al 2009)  Paenibacillus sp . EA00124.565014562 c n.s.(Kim et al 2010)  Rhodococcus erythropolis 22.9725 e 4.8417 c Half-life = 64.4 min300 mM 25 °C(Kullartz and Pietruszka 2012)  Haemophilus influenza 23.67.5400.1470.42 b Maximal activity at 300 mM(Woo et al 2014)  Staphylococcus epidermidis 29.2n.s.67.1 c 11.3% retention of activity2 h 300 mM 25 °C(Fei et al 2015)  Lactobacillus brevis ECU8302n.s.6403.34102 b Half-life = 37.3 min300 mM 25 °C(Jiao et al 2015)Extremophiles (hyperthermophilic unless specified)  Aeropyrum pernix 24.56.5n.s.0.057**4.5 c **n.s.(Sakuraba et al 2003)  Thermococcus kodakaraensis 24.54950.81***285 b ***n.s.(Rashid et al 2004)  Pyrobaculum aerophilum 24.56n.s.0.0660.25 c 53% retention of activity20 h 300 mM 25 °C(Sakuraba et al 2007)  Thermotoga maritima 27.86.5n.s.0.021 c 46% retention of activity20 h 300 mM 25 °C(Sakuraba et al 2007)  Hyperthermus butylicus 26.45.5800.150.5 c 75% retention of activity8 h 300 mM 25 °C(Wang et al 2010)  Aciduliprofundum boonei 26.67800.12n.s.70% retention of activity4 h 250 mM 25 °C(Yin et al 201...…”
Section: Substrate Specificitymentioning
confidence: 99%
“…This will trigger the continuous search for the more efficient, cheaper, and sustainable synthesis of statins [137] and in particular super-statins. This has already been reflected in some reports that have appeared in the literature since this review was written [138][139][140][141][142][143][144]. …”
Section: Assembly Of Pitavastatinmentioning
confidence: 64%